Features of the simultaneous course of pulmonary aspergillosis and tuberculosis on the background of type 1 diabetes mellitus (clinical case) - Raznatovska, О. М.; Myronchuk, Yu. V.; Shalmin, O. S.; Fedorets, A. V.; Svitlytska, O. A.; Разнатовська, Олена Миколаївна; Мирончук, Юлія Валеріївна; Шальмін, Олександр Самуілович; Федорець, Андрій Васильович; Світлицька, Оксана Анатоліївна (Запорізький державний медичний університет, 2022)
Aim. To analyze the features of the simultaneous course of pulmonary aspergillosis and multidrug-resistant pulmonary tuberculosis (MDR-TB) on the background of type 1 diabetes mellitus, on the example of a clinical case of our practice. Materials and methods. Clinical case of our practice of simultaneous pulmonary aspergillosis and MDR-TB on the background of type 1 diabetes mellitus in a patient, who was treated in Pulmonary tuberculosis department No. 2 of clinical base of Phthisiatry and Pulmonology Department of Zaporizhzhia State Medical University at Communal Non-Commercial Enterprise of the “Zaporizhzhia Regional Clinical and Diagnostic Center of Phthisiatry and Pulmonology” of Zaporizhzhia Regional Council. Results. In the presented clinical case, the patient had been suffering from diabetes mellitus for 8 years and had been receiving insulin therapy for all these years. One year before the TB disease, he had contact with an index patient, but he categorically refused a course of preventive chemotherapy. Also, the patient did not make a comparison X-ray TCO after 6 months, as a contact person. MDR-TB and aspergilloma of the left lung of the patient were diagnosed simultaneously on the background of severe condition with decompensated form of type 1 diabetes mellitus, severe intoxication syndrome and inflammatory process, massive hemoptysis. Aspergilloma of the left lung was diagnosed using X-ray TCO and cultural examination of bronchial aspirate for Aspergillus, which was not difficult to diagnose. Diagnosis of MDR-TB was also not difficult, because the patient had MBT, which contributed to the timely and correct appointment of antimycobacterial therapy. Surgery for aspergilloma of the left lung was contraindicated, as the type 1 diabetes was in decompensation. Persistent hyperglycemia remained, despite the fact of antifungal therapy and constant correction of insulin therapy prescribed for the patient. Endocarditis quickly developed in the patient, which was the reason of patient’s death. Мета роботи – на клінічному випадку власного спостереження проаналізувати особливості одночасного перебігу легеневого аспергільозу та мультирезистентного туберкульозу (МР ТБ) при цукровому діабеті 1 типу. Матеріали та методи. Наведено клінічний випадок власного спостереження одночасного перебігу легеневого аспергільозу та МР ТБ у пацієнта з цукровим діабетом 1 типу, який перебував на лікуванні у відділенні легеневого туберкульозу № 2 на клінічній базі кафедри фтизіатрії і пульмонології Запорізького державного медичного університету КНП «Запорізький регіональний фтизіопульмонологічний клінічний лікувально-діагностичний центр» ЗОР. Результати. Пацієнт, клінічний випадок якого наведено, мав цукровий діабет 1 типу протягом 8 років, отримував терапію інсуліном. За рік до захворювання на МР ТБ мав контакт з індексним пацієнтом, але від курсу профілактичної хімієтерапії категорично відмовився. Також хворий не зробив контрольну рентгенограму органів грудної порожнини (РГ ОГП) як контактна особа через 6 місяців. МР ТБ та аспергільому лівої легені в пацієнта діагностували одночасно на тлі тяжкого стану з декомпенсованою формою цукрового діабету 1 типу, вираженим інтоксикаційним синдромом і запальним процесом, масивним кровохарканням. Асергільому лівої легені виявили за результатами РГ ОГП та культурального дослідження аспірату з бронхів на Aspergillus, під час діагностики труднощі не виникли. Діагностика МР ТБ також не складна, оскільки пацієнт був бактеріовиділювачем. Це сприяло своєчасному і правильному призначенню антимікобактеріальної терапії. Оперативне втручання з приводу аспергільоми легені було протипоказане через декомпенсований стан цукрового діабету 1 типу. Незважаючи на те, що пацієнтові призначили протигрибкову терапію, постійно здійснювали корекцію інсулінотерапії, зберігалася стійка гіперглікемія. У хворого швидко розвинувся ендокардит, що спричинив смерть.
Особливості одночасного перебігу легеневого аспергільозу та туберкульозу при цукровому діабеті 1 типу (клінічний випадок)
Raznatovska O. M. - ORCID ID: 0000-0003-2252-9063; Myronchuk Yu. V. - ORCID ID: 0000-0002-4608-2991; Shalmin O. S. - ORCID ID: 0000-0002-1727-0408; Fedorets A. V. - ORCID ID: 0000-0003-0994-5265; Svitlytska O. A. - ORCID ID: 0000-0003-4987-8458.
Keywords: pulmonary aspergillosis; MDR tuberculosis; type 1 diabetes mellitus; легеневий аспергільоз; мультирезистентний туберкульоз; цукровий діабет 1 типу